Capital movements between the European Union and Turkey within the integration processes - Janina Witkowska (Comparative Economic Research. Central and Eastern Europe, 2014)
The institutional model used in the integration process between the European Union (EU) and Turkey was that of establishment of a customs union under an Association Agreement. In the context of the difficulties that have occurred in the membership negotiations between the EU and Turkey, the question arises whether real economic integration between them has gone further than that achieved at the stage of a customs union. Free movement of capital, constituting one of the so-called four fundamental freedoms within the single European market, is the subject of examination in this paper. The obligations of Turkey, as an EU candidate country, in the field of free movement of capital are more demanding under the EU scheme of liberalization of capital flows than within the OECD, which is regulated by the Code of Liberalisation of Capital Movements and the Code of Liberalisation of Current Invisible Operations. Real economic integration between the EU and Turkey requires further liberalization of the free movement of capital. While Turkey encourages the inflow foreign direct investment using a generous package of incentives, the role of FDI in its economy still remains moderate.
Keywords: 330; European Union; Turkey; integration processes; capital movements; foreign direct investment